The Makepeace chronicle : an account of the remarkable life of John Swiftarrow Makepeace - Golsby, Kevin (Sydney, [New South Wales] : Lime Books, 2016)
"The Makepeace Chronicle is a fast moving adventure and love story, spanning almost fifty years through the turn of the 20th century. The narrative is shared by father and son, John and Richard Makepeace, against a backdrop of historical events, extending from the plains of the American North-West and the gold diggings of Ballarat, Australia to the San Francisco earthquake of 1906, the trenches of World War One and an international mid-ocean disaster in the North Atlantic." --Back cover.
Text and colour illustrations on end papers.
Keywords: Biographical fiction; Australian; Historical fiction; Biographical fiction; Historical fiction